2021
DOI: 10.1021/acsapm.1c00929
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of a Robust, High Strength, and Mildew Resistant Fully Biobased Adhesive from Agro-Industrial Wastes

Abstract: Recent decades have witnessed an increasing trend of replacing conventional formaldehyde-based adhesives with sustainable and ecofriendly biobased adhesives in the commercial wood industry. The present study developed a full biomass utilization design for adhesives consisting of a cheap soybean meal and a lignin-based crosslinking agent (EXL). The primary component of the latter, i.e., epoxidized lignin, was synthesized using alkaline lignin and epichlorohydrin under simple reaction conditions. The Fourier tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…It indicated that 8% of CBE was too much for cross-linking soybean protein. The reactions between soybean protein and CBE will form a three-dimensional cross-linking structure, resulting in the improvement of mechanical properties and wet-cohesion of the cured CBE-modified soybean protein-based adhesives [ 25 , 26 ]. However, the residual CBE in the cured adhesive might have acted as a plasticizer to decline its mechanical properties.…”
Section: Resultsmentioning
confidence: 99%
“…It indicated that 8% of CBE was too much for cross-linking soybean protein. The reactions between soybean protein and CBE will form a three-dimensional cross-linking structure, resulting in the improvement of mechanical properties and wet-cohesion of the cured CBE-modified soybean protein-based adhesives [ 25 , 26 ]. However, the residual CBE in the cured adhesive might have acted as a plasticizer to decline its mechanical properties.…”
Section: Resultsmentioning
confidence: 99%
“…Scientists have studied a variety of bio-based adhesives, including starch, 8 soy protein, 9 cottonseed protein, 10 tannin, 11 and lignin. 12 Among these materials, soy protein is especially attractive because it is renewable, biodegradable, economical, can be obtained in high yield, and is rich in reactive functional groups. 13 However, soy protein adhesives have a number of shortcomings, including poor water resistance, low bonding strength, easy deterioration, and susceptibility to mold, all of which have large adverse effects on the durability and bonding strength of the product.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, bio鈥恇ased adhesives have attracted the attention of the research community. Scientists have studied a variety of bio鈥恇ased adhesives, including starch, 8 soy protein, 9 cottonseed protein, 10 tannin, 11 and lignin 12 . Among these materials, soy protein is especially attractive because it is renewable, biodegradable, economical, can be obtained in high yield, and is rich in reactive functional groups 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Trialdehyde adhesive (urea formaldehyde resin, melamine formaldehyde resin, and phenolic resin) was widely used in the traditional wood industry [ 1 ]. However, trialdehyde adhesive had some problems, such as relying on oil resources, releasing formaldehyde, and polluting the environment [ 2 ].…”
Section: Introductionmentioning
confidence: 99%